Preparation and investigation of copper–manganese mixed oxides as a high-efficiency catalyst for the azide-alkyne 1, 3-dipolar cycloaddition reaction. (1st March 2019) - Amini, Mojtaba; Salmani, Somaiyeh; Gautam, Sanjeev; Chae, Keun Hwa
Graphical abstract: The azide-alkyne 1, 3-dipolar cycloaddition reaction to produce 1, 2, 3-triazoles in the presence of copper–manganese mixed oxides nanoparticles were studied. Abstract: The present work is developed for the catalysis of azide-alkyne 1, 3-dipolar cycloaddition reaction with the aid of copper–manganese mixed oxides nanoparticles. The Cu/MnOx nanoparticles have been synthesized by a coprecipitation procedure. Characterization of Cu/MnOx nanoparticles was performed by various spectroscopic techniques, such as powder XRD, Energy dispersive X-ray spectroscopy (EDX) and SEM and TEM analyses. The azide-alkyne cycloaddition reactions successfully proceed under air in presence of the as-prepared copper–manganese mixed oxides nanoparticles. The methodology is advisable to a wide variety of various alkynes and benzyl halide moieties signifying its well suitability.